2016
DOI: 10.1534/g3.116.034744
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Backbone of the Saccharomycotina Yeast Phylogeny Using Genome-Scale Data

Abstract: Understanding the phylogenetic relationships among the yeasts of the subphylum Saccharomycotina is a prerequisite for understanding the evolution of their metabolisms and ecological lifestyles. In the last two decades, the use of rDNA and multilocus data sets has greatly advanced our understanding of the yeast phylogeny, but many deep relationships remain unsupported. In contrast, phylogenomic analyses have involved relatively few taxa and lineages that were often selected with limited considerations for cover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
173
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(195 citation statements)
references
References 90 publications
(147 reference statements)
18
173
2
2
Order By: Relevance
“…Surprisingly, one of the resolved internodes concerned the placement of the CUG-Ser2 clade, which was equivocal in previous phylogenomic studies (Riley et al, 2016; Shen et al, 2016a, 2017). For example, the most recent phylogenomic analysis, in which the CUG-Ser2 clade was represented by a single taxon, showed that the clade’s placement was unduly influenced by inclusion of the DPMI (in S. cerevisieae) gene (Shen et al, 2017).…”
Section: Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…Surprisingly, one of the resolved internodes concerned the placement of the CUG-Ser2 clade, which was equivocal in previous phylogenomic studies (Riley et al, 2016; Shen et al, 2016a, 2017). For example, the most recent phylogenomic analysis, in which the CUG-Ser2 clade was represented by a single taxon, showed that the clade’s placement was unduly influenced by inclusion of the DPMI (in S. cerevisieae) gene (Shen et al, 2017).…”
Section: Resultscontrasting
confidence: 58%
“…The new phylogeny divides the subphylum into 12 major clades (Figure 2), at least two and up to eight more than previously recognized (Dujon and Louis, 2017; Hittinger et al, 2015; Kurtzman and Boekhout, 2017; Kurtzman et al, 2011; Shen et al, 2016a). Several families are now well circumscribed (e.g., Pichiaceae), while other families are not reciprocally monophyletic (e.g., Dipodascaceae/Trichomonascaceae), leading us to consider them as major clades comprised of multiple known families.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…It is likely that the two-locus system corresponds to a simpler ancestral mechanism of switching (Hanson et al 2014), and this conclusion is supported by the existence of switching by inversion in both A. rubescens and the methylotrophs, regardless of which of the proposed phylogenetic positions of A. rubescens is correct (Riley et al 2016; Shen et al 2016). …”
Section: Multiple Mechanisms Of Yeast Mating-type Switchingmentioning
confidence: 98%
“…Based on Riley et al (2016), with placement of A. rubescens as in Shen et al (2016). Mating-type switching does not occur in species with only one MAT -like locus or in Aspergillus nidulans , which is a primary homothallic species.…”
Section: Rewiring Of the Logic Circuit After Whole-genome Duplicationmentioning
confidence: 99%